Islamic Work Ethic As A Model Of Islamic Management Theology - Irfan Goffary (International Journal of Nusantara Islam, 2022)
The integration of Religious Sciences and General Sciences has attracted the attention of Islamic scientists since, Various researches by Muslim scholars have proposed concepts that strengthen the Integration of Science and Religion as an established scientific paradigm. Conceptually, there are at least two big ideas: Al-Faruqi's Islamization of Science and Kuntowijoyo's Islamization of Science. While practically there is IWE (Islamic Work Ethics) which lowers the concept of work ethics from the Al-Quran to the scientific realm. This paper attempts to connect IWE with two trends in the integration of knowledge paradigms: the Islamization of Islam and the Islamization of science. After realizing this, this paper attempts to formulate a scientific work pattern for the IWE theorizing process which can become a scientific work model for the Islamization of science for other concepts.